Pengaruh Musim Liburan dan Promosi Digital terhadap Keputusan Berkunjung The Lawu Park di Solo Raya - Afnia Ayu Safitri; Muhammad Syihabuddin (Pusat Riset dan Inovasi Nasional, 2026)
This study analyzes the effect of holiday seasons and digital promotion on visitors’ decisions to visit The Lawu Park in the Solo Raya region. A quantitative explanatory approach was employed to examine the relationship between seasonal factors, digital marketing, and tourist decision-making. Data were collected through an online questionnaire distributed to 124 respondents who had the potential or experience to visit The Lawu Park. The holiday season variable was measured through indicators of leisure time availability and holiday frequency, while digital promotion was assessed based on social media advertising, promotional programs, interactivity, and ease of information access. The data were analyzed using multiple linear regression after passing validity, reliability, and classical assumption tests. The results indicate that both the holiday season and digital promotion have a positive and significant influence on visiting decisions. Holiday periods provide greater opportunities for travel, while digital promotion strengthens destination awareness and tourist confidence. These findings emphasize the importance of integrating digital promotion strategies with holiday momentum to enhance tourist visits and support effective tourism marketing management.